Impact of heliotherapy and phototherapy on the course of atopic dermatitis - Aleksandra Mańkowska; Monika Truchta; Agata Kolano; Wiktoria Jabłońska; Marta Wardęszkiewicz; Amelia Kasprzak; Szymon Markowiak; Maciej Świercz; Anna Pejas (Kazimierz Wielki University, 2024)
Introduction and purpose. Atopic dermatitis (AD) is a common chronic inflammatory skin disease that affects many children and adults around the world. It has been also empirically known that some environmental factors such as exposure to the sun can be beneficial for patients with AD. The purpose of this literature review is to present positive impact, as well as challenges and risks of heliotherapy and phototherapy on patients suffering from AD. Material and methods. The article is a review of publications obtained from the PubMed database and published between 2017-2023. Based on the keywords "phototherapy" "heliotherapy"and "atopic dermatitis", 14 articles were selected. Finally, 1 meta-analysis and 3 observational studies were included in the rewiev. Brief description of the state of knowledge. People with AD have a compromised skin barrier, which favors infiltration by activated Th2 cells, and their cytokine, causing thickening of the skin. It makes management of AD challenging. It is known that most patients' skin condition improves due to sun exposure. This is why an artificial UV radiation (UVR) is employed for the treatment. The idea is to administrate a non-ionizing radiation to the skin. Both sunlight and artificial light have a significant immunosuppressive effect on the skin. Summary. Phototherapy as well as heliotherapy improved skin condition of people suffering from AD. It was appreciable by the end of few weeks of studies and also afer 3 months, reflected by improvement in PO-SCORAD, VAS and DLQI scales. During some of the studies there have been incidents of side-effects. More research is necessary to define a long-term effect of this kind of treatment and the role of chronic and prolonged therapy of AD.